Digital placemaking and networked corporeality: Embodied mobile media practices in domestic space during Covid-19. (June 2021) - Hardley, Jess; Richardson, Ingrid
In contemporary life, the mobile phone is integral to digital and material placemaking practices. In this article, drawing on ethnographic analysis conducted in Perth and Melbourne (Australia) in the first months of the coronavirus (Covid-19) pandemic, we explore how this relation has been recalibrated as an effect of 'stay-at-home' restrictions. We first provide a brief overview of our methodological and interpretative approach – drawing from postphenomenology as a useful framework for understanding the mobile–body–place relation and digital placemaking at home. Second, we consider how mobile media are 'situated' in the domestic environment. Third, through an analysis of participant narratives, we explore the concept of net locality (Gordon and de Souza e Silva (2011) through the lens of embodiment theory and suggest that the Covid-19 context has altered our experience of 'networked corporeality'. Finally, we discuss the ambiguity of digital intimacy in the decoupling of mobile media and the body as a result of a rapid increase in both screen time and time spent at home. Throughout the article, we argue that mobile media use in the home is thoroughly enmeshed in the shifting boundaries of privacy, placemaking and domestic space. We question how the placemaking functionality of mobile media, the intimate body–technology relation specific to mobile media practices and 'being-at-home' were subsequently modified by physical distancing and isolation.